Integrating Ethnopedagogy in Economic Activities: A Case Study of Rice Farming in the Ciptagelar Community - Khoerunnisa, Tasya; Son, Quang Van (Journal of Basic Education Research, 2024)
Purpose of the Study: This research aims to explore the role of ethnopedagogy in shaping the economic activities of the Ciptagelar community, particularly within the context of rice farming. By examining traditional educational practices, the study seeks to understand how local wisdom is integrated into economic life, contributing to sustainable development and intergenerational knowledge transfer. Methodology: The study employs a descriptive qualitative approach using a case study method to gain an in-depth understanding of the lived experiences of the Ciptagelar community. The research involved seven key informants, including members of the Rorokan and local farmers. Data were collected through interviews, observations, and documentation, focusing on the intersection of education and economic practices in this traditional community. Main Findings: The findings demonstrate that ethno-pedagogy plays a central role in the economic activities of the Kasepuhan Ciptagelar, particularly in rice farming. Critical elements of Ethno pedagogy, such as planning, creating a conducive learning environment, material selection, and inheritance of knowledge, are closely tied to rice farming. For example, rice farming is planned meticulously, with harvests limited to once a year, and harvested rice is prohibited from being sold, ensuring sustainability. Novelty/Originality of this Study: This study offers a novel perspective by integrating ethnopedagogy into the analysis of economic activities. It reveals how traditional learning processes influence sustainable agricultural practices. It underscores the importance of cultural education in preserving economic self-sufficiency and provides a unique model for community-based education rooted in local wisdom.